APLIKASI KRIPTOGRAFI PESAN MENGGUNAKAN ALGORITMA VIGENERE CIPHER - Efrandi Efrandi; Asnawati Asnawati; Yupiyanti Yupianti (UNIVED Press, 2014)
The rapid advances in technology now makes a wide variety of communication servicesgrow by leaps and bounds. One of the most important thing in communication using computers and computer networks is to ensure the security of mes-sages, data, orinformation in the data exchange process, thus becoming one of the drivers of the emergence of cryptography technology. Cryptographic algorithms based on dataencoding information that supports the needs of two aspects of information security, namely secrecy (protection of data confidentiality of information) and authenticity (pro-tection against forgery and alteration of information that is not desirable. Application of theory-the theory gained in the college in making this application in order to implement an encrypted message to be more secure. In making the applica-tion of this cryptosystem, the method used is the Vigenere Cipher, one other form of encryption of type polyal-phabetic. Applications created with Visual Basic 6.0 software and the creation of applications with encryption is expected to settlethe problems mentioned aboveKeywords: Keywords: cryptography, Vigenere ciphe, Visual Basic 6.0